Additive manufacturing of polymer-based structures by extrusion technologies. Issue 1 (23rd October 2020) - Maguire, Alianna; Pottackal, Neethu; Saadi, M A S R; Rahman, Muhammad M; Ajayan, Pulickel M
Abstract: Extrusion-based additive manufacturing (AM) enables the fabrication of three-dimensional structures with intricate cellular architectures where the material is selectively dispensed through a nozzle or orifice in a layer-by-layer fashion at the macro-, meso-, and micro-scale. Polymers and their composites are one of the most widely used materials and are of great interest in the field of AM due to their vast potential for various applications, especially for the medical, military, aerospace, and automotive industries. Because architected polymer-based structures impart remarkably improved material properties such as low density and high mechanical performance compared to their bulk counterparts, this review focuses particularly on the development of such objects by extrusion-based AM intended for structural applications. This review introduces the extrusion-based AM techniques followed by a discussion on the wide variety of materials used for extrusion printing, various architected structures, and their mechanical properties. Notable advances in newly developed polymer and composite materials and their potential applications are summarized. Finally, perspectives and insights into future research of extrusion-based AM on developing high-performance ultra-light materials using polymers and their composite materials are discussed.